The limits of gamification in architecture teaching. The Escape Room technique - Onecha Pérez, Belén; Sanz Prat, Javier; López Valdés, Daniel (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
Currently, a great part of the university community agrees with the statement that “Learning is not a game, but you learn by playing”. It is undeniable that current generations of university students have grown up surrounded by the gamification applied to activities of the more disparate and, as a consequence, have developed the predisposition to the game, since it provides pleasure and happiness, as well as the skills necessary to participate in it, competitiveness, decisive attitude, team spirit and many more. With this perspective in mind and with the aim of highlighting the most important concepts that have been taught during the course, the team of professors of the subject “Basis for Technique” of the first course in the Barcelona School of Arquitecture (Polytechnic University of Catalonia), we have developed a game based in the Escape Room technique. This article describes the methodology of the tests carried out for more than 500 students during 3 courses, analyzes the results regarding the fulfillment of the proposed didactics objectives and proposes a reflection on the limits of the gamification applied to the teaching of architecture.